2003
DOI: 10.1053/jhep.2003.50186
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone induces p27Kip1-associated cell-cycle arrest through down-regulating Skp2 in human hepatoma cells

Abstract: Increasing evidence has confirmed that ligands for peroxisome proliferator-activated receptor ␥ (PPAR␥) exhibit antitumoral effects through inhibition of cell proliferation and induction of cell differentiation in several malignant neoplasms. Recently, we have documented the accumulation of a cyclin-dependent kinase inhibitor, p27 Kip1 , as well as an unexpected accumulation in cyclin E in G1-arrested human hepatoma cells treated with the PPAR␥ ligand troglitazone. Simultaneous accumulations in both p27 Kip1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 39 publications
4
41
0
Order By: Relevance
“…Taken together, re-evaluation of the prognostic significance for p27 expression in malignant neoplasms may be required, paying close attention to its subcellular localization. Although this study included relatively a small number of patients with DLBCL, the results provided deep insights into a new cell-cycle-based strategy for the treatment of DLBCL by precisely targeting Skp2 [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Taken together, re-evaluation of the prognostic significance for p27 expression in malignant neoplasms may be required, paying close attention to its subcellular localization. Although this study included relatively a small number of patients with DLBCL, the results provided deep insights into a new cell-cycle-based strategy for the treatment of DLBCL by precisely targeting Skp2 [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Hep3B cells (80% confluent) were exposed to 100 lM rosiglitazone for various times (3,8,12, or 24 hours). The PPARc/DNA binding activity in nuclear extract was measured using an enzyme-linked immunosorbent assay (ELISA)-based assay (Cayman Chemical, Ann Arbor, Mich).…”
Section: Pparc Binding Activity Assaymentioning
confidence: 99%
“…6 We and others previously showed that rosiglitazone, a thiazolidinedione-class drug, inhibited hepatocarcinogenesis in vitro and in vivo by inducing cell apoptosis and cell cycle arrest. [7][8][9] However, the PPARc regulatory network and its molecular targets in liver cancer remain largely unknown. In this study, we identified the PPARc downstream targets relevant to carcinogenesis, by using oligonucleotide microarray and gene ontology analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Skp2 expression is also affected by treatment with retinoic acid, thus altering the ability of p27 to be ubiquitinated (Nakamura et al, 2003). Troglitazone belongs to a group of ligands for peroxisome proliferator-activated receptor gamma (PPARgamma) (Koga et al, 2003). Its antitumoral effects in human hepatoma cells are also due to a decreased gene expression of Skp2 at the mRNA level, leading to the accumulation of p27 (Koga et al, 2003).…”
Section: Targeted Therapymentioning
confidence: 99%
“…Troglitazone belongs to a group of ligands for peroxisome proliferator-activated receptor gamma (PPARgamma) (Koga et al, 2003). Its antitumoral effects in human hepatoma cells are also due to a decreased gene expression of Skp2 at the mRNA level, leading to the accumulation of p27 (Koga et al, 2003). Targeting the APC by specific inhibitors of the multiple subunits is another very promising approach for a more specific cancer therapy and subject of ongoing research.…”
Section: Targeted Therapymentioning
confidence: 99%